A short report: reflective testing in the diagnosis of hereditary haemochromatosis: results of a short retrospective study. (May 2019) - Malton, Katie; Turnock, Daniel
Background: Reflective addition of iron studies to elevated ferritin results can be a useful first step towards making a diagnosis of haemochromatosis; however, the criteria for doing so are poorly defined and the efficiency of different stages of this process are not well documented. We studied the efficiency of current practice at York Teaching Hospitals NHS Foundation Trust with the aim to identify areas for improvement. Methods: Data were gathered from the laboratory database on the number of iron studies and subsequent interpretive comments reflectively added by laboratory staff during an eight-month period. Reflective addition of iron was based on individual practice of the reporter. Standardised interpretive comments were added to suggest HFE genotyping when both the ferritin and transferrin saturation were raised. The number of patients successfully followed up and found to have pathological HFE gene mutations was used to evaluate efficiency. Results: A total of 2651 raised ferritin results were reported during the evaluation period, which resulted in the reflective addition of 381 iron studies and 43 interpretive comments by the duty biochemists. This led to 33 requests for HFE genotyping and the identification of 13 individuals with pathological mutations. The number of iron studies reflectively added to diagnose one patient (NND) was found to be 29.3. Conclusions: Reflective addition of iron studies and interpretive comments can assist in the early detection of patients with hereditary haemochromatosis. Better guidance for laboratory staff undertaking reflective testing and for general practitioners facilitating patient follow-up may increase the efficiency of this diagnostic process.